The Rogue as an Artist in Patrick deWitt’s The Sisters Brothers - Staels, Hilde (Text Matters: A Journal of Literature, Theory and Culture, 2019)
This article explores Eli Sisters as a reinvigorated rogue who finds his artistic calling in Patrick deWitt’s The Sisters Brothers, published in 2011. With the help of insights from narratology and genre theory, the article provides a textual analysis of Eli’s discourse, perspective and behaviour. Eli casts a critical light on the senseless violence, unbridled greed, ecological devastation, and hyper-masculinity inherent to America’s Frontier myth. As a reinvigorated rogue, he raises questions about what it means to be human and reflects upon morality. With hindsight, the rogue as an artist creates a generically hybrid narrative that parodically imitates and transforms the genre conventions of the Western and the picaresque tale. The article also draws attention to the power that Eli assigns to women in a story about male heroic conquest. These include otherworldly female figures from classical mythology and the brothers’ mother.